2018
DOI: 10.3892/mmr.2018.9254
|View full text |Cite
|
Sign up to set email alerts
|

Astragalin and dihydromyricetin as adjuncts to histidine‑tryptophan‑ketoglutarate cardioplegia enhances protection during cardioplegic arrest

Abstract: The present study used an in vitro model of cold cardioplegia in isolated working rat hearts to evaluate the possible effects of two flavonoids, astragalin and dihydromyricetin, as adjuncts to histidine‑tryptophan‑ketoglutarate (HTK) cardioplegia. The following three groups of male Sprague Dawley rats were evaluated: The HTK group, treated with HTK alone; the HTK‑A group, treated with 10 µmol/l astragalin; and the HTK‑D group, treated with 10 µmol/l dihydromyricetin. Isolated rat hearts were perfused with Kreb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Therefore, DHM has been shown to have a variety of beneficial functions in the current study and has become a potential source of treatment of CIRI. A previous study investigating ischemia reperfusion injury found that DHM enhances protection during ischemia, decreases myocardial dysfunction by enhancing anti-inflammatory activities, attenuates myocardial oxidative injury and prevents apoptosis during ischemia/reperfusion (22). In a study investigating cerebral ischemia, DHM was found to effectively prevent cerebral edema caused by whole brain I/R injury in rats caused by the ligation of the bilateral common carotid artery (23).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, DHM has been shown to have a variety of beneficial functions in the current study and has become a potential source of treatment of CIRI. A previous study investigating ischemia reperfusion injury found that DHM enhances protection during ischemia, decreases myocardial dysfunction by enhancing anti-inflammatory activities, attenuates myocardial oxidative injury and prevents apoptosis during ischemia/reperfusion (22). In a study investigating cerebral ischemia, DHM was found to effectively prevent cerebral edema caused by whole brain I/R injury in rats caused by the ligation of the bilateral common carotid artery (23).…”
Section: Discussionmentioning
confidence: 99%
“…Astragalin isolated from mulberry leaves by glycosides could reduce hemolysis of red blood cells induced by oxygen free radicals (Choi et al, 2013). As auxiliary components, astragalin and dihydromyricetin can enhance the protective effects of histidine, tryptophan, and ketoglutarate during cardiac arrest (Wang et al, 2018). However, the anti-tumor activity of ASG and their main mechanism have rarely been reported.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of IL-6 was also obviously reduced. Thereby, AST alleviated the inflammatory response caused by oxidative stress [64][65][66]. Furthermore, AST also showed promise in improving brain I/R injury.…”
Section: The Effect Of Astragalin On the Ischemia-reperfusion Injury ...mentioning
confidence: 96%